An Audio Visual Learn Care For UUM - Alzyadat, Wael Jumah Abdel Latif (2008)
Conducting study in a classroom has been an old method of teaching and learning process. In a typical way lecturer gives lecture and student takes notes and some times participate during class lecture. Essential time constraint, confinement of basic ideas and lack of interactive training aids make it bulky for students to cope up with new ideas being taught. Audio visual cyber Learning is relatively a new concept, involving on-line teacher and student interaction, information from related web-sites, and student-student chatting. Where the participants of diverse background can share different points of views on complex issues, coherent analysis and generates well-articulated and well-reasoned thoughts on core issues. Cyberspace interaction can surely help achieve the reformation, improvement and extension of quality education. This paper presents the technologies, infrastructure and will implement audio visual E-Learning learn care for UUM. Special emphasis will be on third world countries where economic constraint is the major hindrance in adopting technology. The online distance learning techniques or E-Learning, now in use worldwide, are presented together with a summary of their evaluation. The concept of ever-present computing on campus and off-campus in the future is the motif of this paper. The paper gives an over view of basic parameters and limitation of typical higher-education distance learning and teaching schemes. The benefits and limits of distance learning approach for the basic services, lessons, seminars and tutoring will be discussed. Finally, new concept of learning will be discussed as to how a UUM student can learn interactively by being a student of UUM .